Beam Alignment for mmWave Using Non-Stationary Bandits - Gupta R.; Lakshmanan K.; Sah A.K. (My University, 2025)
A wireless system communicating in the millimeter-wave (mmWave) band suffers from severe propagation loss and thus, employs a highly directional beam to mitigate the effect of propagation losses. However, such beams need to be aligned between the transmitter and receiver for any reliable communication to occur. In literature, this problem has been modeled as a multi-armed bandit. Most of the existing solutions for this problem use stationary bandit algorithms, which suit for time-invariant channels, whereas wireless channels are time-variant in nature. Thus, we propose two non-stationary multi-armed bandit based beam alignment BA algorithms, especially designed for time-varying channels. These algorithms perform a distributed BA between the transmitter and the receiver requiring minimal feedback. Using simulations, we have shown that the proposed BA algorithms minimize the outage probabilities and the regret compared to those of the exponential-weights algorithm. © 1997-2012 IEEE.